Exploration, Religion and Empire in the Sixteenth-century Ibero-Atlantic World A New Perspective on the History of Modern Science - Nieto Olarte, Mauricio (Maritime Humanities, 1400-1800, 2021)
The Iberian conquest of the Atlantic at the beginning of the sixteenth century had a notable impact on the formation of the new world order in which Christian Europe claimed control over most a considerable part of the planet. This was possible thanks to the confluence of different and inseparable factors: the development of new technical capacities and favorable geographical conditions in which to navigate the great oceans; the Christian mandate to extend the faith; the need for new trade routes; and an imperial organization aspiring to global dominance. The author explores new methods for approaching old historiographical problems of the Renaissance - such as the discovery and conquest of America, the birth of modern science, and the problem of Eurocentrism - now in reference to actors and regions scarcely visible in the complex history of modern Europe: the ships, the wind, the navigators, their instruments, their gods, saints, and demons